In-situ growth of LiFePO4 nanocrystals on interconnected carbon nanotubes/mesoporous carbon nanosheets for high-performance lithium ion batteries. (20th January 2015) - Wu, Ruofei; Xia, Guofeng; Shen, Shuiyun; Zhu, Fengjuan; Jiang, Fengjing; Zhang, Junliang
Graphical abstract: In-situ soft-templated LFP nanocrystals on interconnected carbon nanotubes/mesoporous carbon nanosheets (designated as LFP@CNTs/CNSs), exhibited superior electrochemical performance due to the synergetic effect between CNTs and CNSs, which form interconnected conductive network for fast transport of both electrons and lithium ions. Highlights: LFP nanocrystals were in-situ synthesized on interconnected CNTs/CNSs framework with an in-situ soft-templated method. LFP@CNTs/CNSs exhibited superior rate capability and cycling stability, due to interconnected conductive network for fast transport of both electrons and lithium ions. The synergetic effect between CNTs and CNSs on the electrochemical performance of LFP electrode was demonstrated by a systematically electrochemical study compared with LFP/CNSs and LFP/CNTs. Abstract: Lithium ion phosphate (LiFePO4 ) nanocrystals are successfully in-situ grown on interconnected carbon nanotubes/mesoporous carbon nanosheets (designated as LFP@CNTs/CNSs) with a soft-templated method, which involves the multi-constituent co-assembly of a triblock copolymer, CNTs, resol and precursors of LFP followed by thermal treatment. X-ray diffraction, scanning electron microscopy, high resolution transmission electron microscopy and N2 adsorption-desorption techniques are used to characterize the structure and morphology of the as-synthesized materials. When used as the cathode of lithium ion batteries, the LFP@CNTs/CNSs composite exhibits superior rate capability and cycling stability, compared with the samples modified only with CNSs (designated as LFP/CNSs) or with CNTs (designated as LFP/CNTs). This is mainly attributed to the synergetic effect between CNTs and CNSs caused by their unique structure, which forms interconnected conductive network for fast transport of both electrons and lithium ions, and thus remarkably improves the electrode kinetics. Firstly, nano-sized LFP are in-situ grown on the CNTs/CNSs framework, which can serve as an effective matrix to (i) restrain the size growth of LFP during the thermal treatment process and (ii) prevent them from aggregating during cycling. Secondly, the incorporation of CNTs/CNSs framework into the LFP electrode significantly increases the electronic conductivity of the composite, and thus allow for improved high-rate charge-discharge performance. Finally, open mesoporosity in the CNTs/CNSs framework also provides an efficient transport pathway for lithium ions diffusion to LFP.